AI’s transformation of digital consumer behaviour in marketing: A PRISMA-guided systematic review and thematic synthesis (2016-2025) - Pallavi, T S; Chithambar, Gupta V (The International tax journal, 2026)
This study examines how artificial intelligence affects digital consumer behaviour in a marketing environment, summarising the existing literature to address gaps in the existing body of knowledge. Based on PRISMA 2020 guidelines, a systematic review of 119 articles indexed in Scopus and published by peer-reviewed journals between the years 2016 and 2025 was conducted. The data were analysed using bibliometric visualisation and thematic synthesis. Findings demonstrate that the level of scholarly output has significantly increased since 2020, which is also reflected by the growing use of chatbots, recommender systems, and generative AI in business interfaces. Determinants identified to be important are trust, perceived risk, privacy, transparency, perceived control and anthropomorphism; and behavioural intention is a mediating factor in adoption and continued use. The review also identifies methodological limitations, including excessive reliance on cross-sectional designs, as well as a lack of cross-cultural and longitudinal views, and poor integration of ethical governance into consumer-behaviour paradigms. This research contributes to existing knowledge on the topic of AI-influenced decision-making and adds value to understanding the necessity of explicable and human-focused AI in marketing.